Laboratory evaluation of twelve portable devices for medicine quality screening - Zambrzycki, SC; Caillet, C; Vickers, S; Bouza, M; Donndelinger, DV; Geben, LC; Bernier, MC; Newton, PN; Fernández, FM (Public Library of Science, 2021)
Background Post-market surveillance is a key regulatory function to prevent substandard and falsified (SF) medicines from being consumed by patients. Field deployable technologies offer the potential for rapid objective screening for SF medicines.